Scientific approaches to developing strategies for modernization of enterprises - Chupryna, Kh.; Nikolayko, D.; Huliaiev, D.; Yakymchuk , T. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the study of scientific approaches to the formulation of modernization strategies of enterprises in the conditions of constant economic changes and technological innovations. With the development of digital technologies, market globalization and the need to adapt to new business realities, enterprises face numerous challenges that require the implementation of modernization strategies to ensure their competitiveness and sustainable development. One of the main problems is the adaptation of traditional management methods to a rapidly changing environment, therefore scientific approaches that involve the integration of new technologies, optimization of resources and the implementation of flexible management solutions are important. The article considers various approaches to the development of modernization strategies, including the application of management innovations, digitalization of processes, increasing the efficiency of the organizational structure and new models of risk management. Particular attention is paid to methods that allow reducing costs, increasing productivity and adapting enterprises to changes in the market. Modernization is not limited to technology upgrades, but also includes significant changes in management culture, corporate structure, and interaction with market partners. From this perspective, the article emphasizes the importance of developing modernization strategies that take into account not only economic, but also social and environmental aspects of enterprise activities, which allows making their activities more stable and balanced. The article also emphasizes the need to integrate innovative technologies into enterprise modernization processes, which is a key factor in success in conditions of dynamic market changes. Enterprise modernization is not limited to technological innovations, it also includes changes in approaches to personnel management, communication between departments, and interaction with customers. The development of flexible and dynamic organizational structures is a necessary condition for successful adaptation to change. Thus, the article provides a comprehensive approach to developing enterprise modernization strategies that helps them remain competitive, adapt to new conditions, and ensure sustainable development.